2020
DOI: 10.5505/tjo.2020.2066
|View full text |Cite
|
Sign up to set email alerts
|

The Estimation of Thyroid Cancer Risk based on Type 2 Diabetes Mellitus and ABO Blood Group

Abstract: Multiple potential risk factors have been proposed for the development of thyroid cancer. Type 2 diabetes and ABO blood group had a significant relationship with some cancers. These agents may be related to thyroid cancer. This study investigates the association between thyroid cancer and diabetes and the ABO blood group. METHODS This analytic study was conducted in patients with thyroid cancer (n=87) and the individuals cancerfree (n=929). The odds ratio of thyroid cancer was estimated in diabetic patients af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Multiple previous studies have shown a of ndings (22)(23)(24)(25). A.H. Mansour et al found that patients with blood type O tend to have a higher risk for thyroid cancer (as well as lymphomas and gastric cancers) than any other type of cancer (22).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Multiple previous studies have shown a of ndings (22)(23)(24)(25). A.H. Mansour et al found that patients with blood type O tend to have a higher risk for thyroid cancer (as well as lymphomas and gastric cancers) than any other type of cancer (22).…”
Section: Discussionmentioning
confidence: 98%
“…Hui-xian Yan et al found that AB blood was more frequently associated with malignant than benign thyroid nodules (23). Others, such as Shahrokh et al and Meiling Huang et al, found that blood type B was more associated with the risk of thyroid cancer (24,25). All these different ndings can raise the conclusion that blood type does not predict the risk of malignancy or the benign nature of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…There is not much research on the association between blood types and the Rh factor in thyroid cancer. Once believed to be a particular marker of PTC cells, the keratan sulfate epitope was shown to be generated concurrently with Poly-N-acetylglucosamine, which contains blood type antigens 16 .…”
Section: Sasmentioning
confidence: 99%